Poverty, Ethics and Justice Revisited. - Lötter, H. (Res Publica (13564765), 2016)
In this article I respond to the thoughtful criticisms of my book articulated by Gillian Brock, Thaddeus Metz, and Darrel Moellendorf. Their critical questioning offers me an opportunity to reformulate aspects of the book so that I more accurately say exactly what I had in mind when writing the book. The first section contains a reworking of my definition of poverty to eliminate any ambiguity and demonstrate what kind of comparative judgements the definition allows us to make. The second section looks anew at the multiple moral sources for our obligation to eradicate poverty. In the third section I focus on issues that could hinder attempts at eradicating poverty. One is the lack of accessible knowledge that might be too demanding to acquire. The other is the possibility that all attempts to eradicate poverty might have to be put on hold until oppressive capitalist development has prepared the circumstances for a more socialist distribution of resources. I argue that neither of these concerns should hinder the eradication of poverty.